Ceramic technology. How to reconstruct the firing process - Gliozzo, Elisabetta (Archaeological and anthropological sciences, 2020)
Focused on uncoated ceramics, this tutorial paper is divided into two main sections. The first section deals with the operational phases required prior to firing (drying, piling, fuel supply). Then, the second chapter deals with the transformations that occur in the clayey paste during firing. An overall understanding of the firing process includes several issues to be considered and properly investigated. Thereafter, the thermal behaviour of several mineralogical phases (calcite and dolomite; quartz and cristobalite; K-feldspar and plagioclase; rutile and anatase; haematite, maghemite, hercynite and metallic Fe; illite, muscovite, biotite and chlorite; wollastonite, melilite, anorthite and monticellite; diopside and kaolinite) is described. Four brief chapters are further dedicated to the development of the amorphous/glassy component, to the matrix and its porosity, to the colour and the organic matter and to the variations in chemical composition, respectively. The concluding remarks provide a short list of the analytical techniques that have been commonly applied to the investigation of firing conditions and a concise summary of the state of the art of the “firing issue”. The method to be applied in future experimental reproductions and the opportunity itself to investigate the “firing issue” in various contexts are further discussed.